Impact of Malnutrition and Inflammation on Mortality in Hemodialysis Patients: A Prospective Study - Ahmad, Zeshan; Muhammad Anees; asif, Izza (Annals of King Edward Medical University, 2026)
Background: Malnutrition and inflammation are common conditions in patients undergoing hemodialysis (HD) that contribute to poor health outcomes, although their impact on mortality among South Asian populations is limited. This paper discusses how these factors interact and how they affect patient survival. Objective: To examine the relationship between malnutrition, inflammation and mortality in HD patients, the relationship between these three variables, as well as their impact on clinical outcomes. Methods: This is a prospective cohort study, which was carried out at the department of Nephrology, Mayo hospital Lahore between September 2023 and October 2024. The sample consisted of 134 patients who were over 18 years old and on maintenance hemodialysis (MHD) for at least three months. Nutritional status was identified using the Malnutrition-Inflammation Score (MIS) and CRP, and ferritin was used to identify inflammation. Anthropometric and biochemical data were recorded at the beginning of the research. Patients were followed for a year, and Kaplan-Meier curves and Cox regression were used as survival outcomes to analyse the results. Results: Among the 134 patients, 82.8% of the patients were malnourished and 38.8% were classified as severely malnutrition (MIS>9). During the one year follow-up period, 17 patients (12.8%) died. Mortality was strongly associated with higher MIS scores and elevated CRP levels (p<0.001). Compared to survivors, deceased patients had lower MAMC, hemoglobin, and albumin, but higher ferritin levels (p<0.05). Conclusion: Malnutrition and inflammation are strongly linked to higher mortality in HD patients. Key indicators are severe malnutrition, elevated CRP and ferritin, and low albumin levels. Regular nutrition screening, effective management of inflammation and early dietary interventions can help reduce mortality risk.